SOCIO-PEDAGOGICAL FUNCTIONS OF PHYSICAL EDUCATION AND SPORT IN THE MODERN EDUCATIONAL SYSTEM (Web of Teachers: Inderscience Research, 2026)
This article provides a scientific analysis of the socio-pedagogical significance of physical education and sport in the development of society, as well as their role in the physical, moral, and intellectual development of the individual. The study highlights the integral relationship between physical education, sport, and national culture, their importance in promoting a healthy lifestyle among the younger generation, and their functions in strengthening social cohesion within society. In addition, the historical stages of the formation of the physical education system, the effectiveness of modern health-improving systems, and the impact of physical activity on the psycho-emotional state of individuals are substantiated. The article also scientifically reveals the relevance of training highly qualified specialists in the field of physical education and sport.